Effects of gender and brain hemisphericity on thinking skill of a group pf lower sixth students - Chua, Y.P. (Education Faculty, University of Malaya, 2008)
The main purpose of this study was to explore the relationships between gender and brain hemispherisity with creative thinking ability of the lower sixth students. Creative thinking ability was measured by the Torrance Test of Creative Thinking (TTCT), while brain hemisphericity was measured by the Styles of Learning and Thinking test (SOLAT). The research instruments were administered to a sample of 216 students which were randomly selected from a population of 2491 lower sixth students in Selangor. By controlling three covariates, i.e.ethnicity, academic major and critical thinking ability using the MANCOVA test, results of the analysis indicated that gender was significantly correlated with creative thinking ability,while right brain thinking and learning style was positively and significantly correlated with all of the five components of creative thinking ability, i.e. originality, fluency, elaboration, abstractness of title and resistance of premature closure. Besides that, the result of the analysis of the Cramer V test indicated that gender was significantly correlated with brain hemisphericity. The results implied that educators should implement creative teaching and learning strategies, instead of emphasizing on the left hemisphericity skills. Since competence in creative thinking and critical thinking skills are essential to nearly every aspect of learning in school, educators should implement whole brain learning strategies,instead of encouraging merely the left, or the right brain learning strategies.